THE EVOLUTION OF CONSUMPTION TAXES AND THEIR IMPACT ON THE ECONOMY: VAT VS SALES TAX - Loso Judijanto; Andrea Basworo Palestho; Hasni Noor; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
The evolution of consumption taxes, particularly Value Added Tax (VAT) and Sales Tax, has played an important role in the country's revenue structure and its impact on the economy. VAT, where tax is levied on value added at every stage of production and distribution, is different from Sales Tax which is levied only at the final stage of sale to consumers. While both taxes aim to generate revenue, they have different mechanisms, administrative efficiency, and economic effects. VAT is considered more effective in generating revenue without disrupting significant economic activity, while Sales Tax is often criticised for its regressive and potentially distortive nature. The study conducted in this research uses literature research method. The results show that while consumption tax provides a stable source of revenue and increases taxpayer compliance, its structure can have a negative impact, particularly on low-income families, due to its regressive nature. Further investigations address the impact of consumption taxes on consumer behaviour and market dynamics, highlighting how the structure of tax rates affects the affordability of goods and consumer choice. Finally, this study offers suggestions for policy formulation with a balanced approach to ensure that the social and economic benefits of consumption taxes are maximised, while mitigating potential unintended consequences that could hamper overall economic growth.